2011
DOI: 10.1111/j.1475-097x.2011.01062.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects on the ventricular function in Swedish snuffers: an echocardiographic study

Abstract: This study shows that snuff intake causes a significant decrease in E/A ratio and a delay in ventricular relaxation and therefore a decrease in diastolic heart function in the left and right ventricles. The mechanism behind these alterations is probably very complex, but a combination of nicotine effects and loading conditions is probably the main factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Otherwise, healthy regular snus users considered free of cardiovascular disease had no significant change in systolic parameters but did have a prolonged deceleration times compared with non-nicotine users. 31 Acute nicotine exposure was also found to cause a significant decrease and delay in relaxation of both right and left ventricles. 32 Studies in healthy subjects have demonstrated acute impairment of LV diastolic function and inducement of a hyperdynamic RV in response to smoking a single cigarette.…”
Section: Discussionmentioning
confidence: 96%
“…Otherwise, healthy regular snus users considered free of cardiovascular disease had no significant change in systolic parameters but did have a prolonged deceleration times compared with non-nicotine users. 31 Acute nicotine exposure was also found to cause a significant decrease and delay in relaxation of both right and left ventricles. 32 Studies in healthy subjects have demonstrated acute impairment of LV diastolic function and inducement of a hyperdynamic RV in response to smoking a single cigarette.…”
Section: Discussionmentioning
confidence: 96%
“…The trend in the study was that almost all of the diastolic heart parameters measured in the nicotine groups were very slightly altered compared with the control group, but the alterations were very modest, and the slightly prolongation of DT may therefore be seen as random. This study thereby confirms that the acute alterations in diastolic heart function that nicotine products induce immediately after usage (Alam et al ., ; Karakaya et al ., ; Ilgenli & Akpinar, ; Barutcu et al ., ; Ciftci et al ., ; Giacomin et al ., ; Dogan et al ., ; Sundström et al ., ) does not seem to induce a permanently decrease in systolic‐ and diastolic cardiac parameters in middle‐aged, long‐term tobacco users (smokers and snuff users) compared with non‐tobacco users. If heavy long‐term tobacco usage will yield more prominent alterations than less heavy long‐term users however still remains unclear, and further and larger studies are needed to confirm whether long‐term tobacco users really have an increased risk of non‐ischaemic heart failure or not.…”
Section: Discussionmentioning
confidence: 96%
“…Previous echocardiographic studies on long‐term snuff usage and heart function are not as far as we know performed or published, and the data from the present study are therefore somewhat difficult to interpret. There is one study published (Sundström et al ., ) that has shown that administration of Swedish snuff initiates an acute alteration in several diastolic heart parameters and therefore an immediate delay in ventricular relaxation just 5 min after administration. The systolic function was unaltered according to that study which indicates that the finding of slightly lower LVEF in snuff users is a random finding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations